2005
DOI: 10.1590/s0101-20612005000300028
|View full text |Cite
|
Sign up to set email alerts
|

Cinética de transferência de massa de melão desidratado osmoticamente em soluções de sacarose e maltose

Abstract: A quem a correspondência deve ser enviada. RESUMO Cubos de melão de 20mm da variedade, cultivar Gold Mine foram desidratados osmoticamente com o objetivo de se estudar a cinética de transferência de massa durante o processo. As amostras foram imersas em soluções hipertônicas de sacarose ou maltose nas concentrações de 40 a 60°Brix e a desidratação foi conduzida por 8 horas com temperatura controlada (30 ou 40°C) e agitação de 120rpm. Perda de água e incorporação de sólidos na fruta foram avaliados ao longo do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
25

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
1
6
1
25
Order By: Relevance
“…As frutas foram selecionadas de acordo com o grau de maturação (11)(12)(13), tamanho e formato (552,4 54,1 g, 11,9 0,5 cm de comprimento e 10,0 0,4 cm diâmetro).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…As frutas foram selecionadas de acordo com o grau de maturação (11)(12)(13), tamanho e formato (552,4 54,1 g, 11,9 0,5 cm de comprimento e 10,0 0,4 cm diâmetro).…”
Section: Methodsunclassified
“…Desvios elevados na determinação da tensão e deformação na ruptura também foram observados em trabalhos realizados com goiabas 24 , maçãs 18 e melão 11 . Assim, o valor da tensão de ruptura foi apresentada normalizada, ou seja, os valores de tensão foram divididos pelos respectivos valores obtidos para a fruta fresca.…”
Section: Tensão E Deformação Na Rupturaunclassified
“…Thus, osmotic dehydration of the star-fruit slices was faster during the first two hours. Ferrari et al (2005), Betoret et al (2004) and Sanjinez-Argandoña (1999), investigating the osmotic dehydration of melon, cassava, and guava, respectively, also observed that the mass transfer occurred more intensely during the first two hours of treatment reaching equilibrium after eight hours of processing.…”
Section: Osmotic Dehydration Kineticsmentioning
confidence: 96%
“…In general, all treatments led to a reduction in browning of the star-fruit (higher L* when compared to the values obtained for the non-treated fruit), independently of the acid concentration used, with the exception of sample number 1, which exhibited luminosity values similar to under different conditions of temperature (T), concentration (C), and initial fruit:solution ratio (F:S) according to a complete 2 3 central composite design with 8 factorial points, 6 axial points, and 4 central points resulting in a total of 18 trials ( Table 2). The process was carried out at a controlled temperature TE-420 orbital shaker (Tecnal, Piracicaba, Brazil), with constant shaking at 120 rpm (FERRARI et al, 2005; PEREIRA; CARMELLO-GUERREIRO; HUBINGER, 2009) and a maximum process time of 8 hours. The samples were submerged in the osmotic solution in 600 mL beakers separately for each pre-determined time intervals.…”
Section: Blanchingmentioning
confidence: 99%
See 1 more Smart Citation